Practices in concurrent engineering - Ellis, L.W.; Curtis, C.C. (Institute of Electrical and Electronics Engineers Inc., 1992)
To describe concurrent engineering, one must remember the old story of blind individuals attempting to characterize an elephant by feeling different body parts. The issue seems not to be just R&D cycle times, but the entire innovation cycle time process from conception of an idea ~ often in marketing not R&D -, to its final delivery to a customer - often through down-stream firms not under the R&D company's control. From the recency of many sources in the literature, this shift to a time orientation is itself rather recent. Two threads seem to have emerged: First, there is a need to address cycle-time reduction on existing products and services, both in manufacturing and administration, as an implementation management issue relating to the order-to-delivery cycle, in which engineering may be a limited associate. Also, necessary is the innovation management issue of reducing the cycle time from marketing concept to proquct introduction into the implementation process, which is the main thrust of concurrent engineering. In late 1991, a survey was conducted, first, to seek to establish a better working definition of cycle time within the two overall areas of current operations and new product development, and second, to determine the relationships between cycle time so defined and company size or profitability. The survey questionnaire was mailed to 99 medium-to-large high technology manufacturing companies in Connecticut, and yielded 48 responses, with 35 of them usable. The results confirmed the impression given by the literature that the concept was better established in current operations than in innovation management. While some do use the concept of cycle time in their new product development sub-cycles, most do not track time spent on either end of the cycle, from idea to design on the near end, or at the far end through shipment and subsequent service to the customer. Measures of size did not correlate with any of the development measures, while they did with some of the operations measures. Thus, while in concept, concurrent engineering appears to be a goal of multi-functional co-operation, a survey of the manner in which a limited number of firms actually operate seems still focused on functional specializations. © 1992 IEEE.
Keywords: Commerce; Concurrent engineering; Cycle time reduction; Environmental management; Implementation managements; Implementation process; Innovation management; Manufacturing companies; Marketing; Marketing concept; New product development; Product design; Product development; Products and services; Surveys; dept.acc

Do managerial efficiency and social responsibility drive long-term financial performance of not-for-profit hospitals before acquisition?. - Phillips, J F (Journal of health care finance, 1999)
Due to steep declines in charitable support and reduced demand for traditional hospital services, economic goals are increasingly important to not-for-profit hospitals. Effects of efficient management and effective pursuit of not-for-profit status (for example, levels of Medicare, indigent patients, and unprofitable services) on financial viability are explored. While previous research compared hospitals of different ownership status, not-for-profit hospital operations before acquisition by for-profit hospital chains are investigated--"neutral ground" relative to ownership. Results suggest minor links between efficiency and long-term profitability despite effectiveness in pursuit of non taxable status.
Keywords: *Efficiency, Organizational; *Financial Management, Hospital; *Hospitals, Voluntary/og [Organization & Administration]; *Social Responsibility; Bed Occupancy; Case mix index; Diagnosis-Related Groups; Efficiency, Organizational; Financial Management, Hospital; Free cash flow accounting valuation; Health Facility Merger; Health Facility Merger/sn [Statistics & Numerical Data]; Hospitals, Voluntary; Hospitals, Voluntary/st [Standards]; Humans; Investor-owned hospital corporations; Least-Squares Analysis; Length of Stay; Length of stay; Managerial efficiency; Median household income; Medicare; Medicare patients; Medicare/sn [Statistics & Numerical Data]; Not-for-profit hospital acquisitions; Occupancy rate; Social Responsibility; Social responsibility; United States; article; dept.acc; financial management; hospital finance; hospital management; hospitalization; length of stay; medicare; profit; social behavior; ⛔ No DOI found

For-profit chains seek to acquire successful not-for-profit hospitals. - Phillips, J F (Healthcare financial management : journal of the Healthcare Financial Management Association, 1999)
Over the last decade, investor-owned hospital corporations have grown primarily by acquiring other for-profit hospital chains or stand-alone for-profit institutions. Between 1990 and 1995, however, these corporations also acquired nearly 50 not-for-profit hospitals and converted them to for-profit status. An examination of the long-term financial condition of 39 not-for-profit hospitals acquired by various investor-owned hospital corporations between 1992 and 1996 was conducted using free-cash-flow accounting valuation. The results suggest that, initially, only not-for-profit hospitals in dire financial straits were candidates for acquisition and conversion to for-profit status. More recent acquisitions increasingly have involved more successful not-for-profit hospitals.
Keywords: *Financial Management, Hospital/td [Trends]; *Health Facility Merger; *Hospitals, Proprietary/ec [Economics]; *Hospitals, Voluntary/ec [Economics]; *Multi-Institutional Systems/ec [Economics]; Accounts Payable and Receivable; Financial Audit; Hospitals, Proprietary/og [Organization & Administration]; Longitudinal Studies; United States; dept.acc; ⛔ No DOI found

Satisfy customers while speeding R&D and staying profitable - Curtis, Carey C; Ellis, Lynn W (Research-technology Management, 1998)
Studies of innovation management effectiveness pinpoint specific practices that will allow companies to increase customer satisfaction and pursue a strategy of speedy R&D-without compromising profitability. The two practices that accomplish this end, when used moderately (although not universally), are Quality Function Deployment for project selection and Stage-Gate Tracking for controlling development. Companies that use Internal Rate of Return as a criterion for project selection have also been found to be move profitable.
Keywords: Customer satisfaction; Industrial economics; Profitability; Quality function deployment; Research and development management; Strategic planning; dept.acc

The influence of career stage on the work attitudes of male and female accounting professionals - Lynn, Susan A; Cao, Le Thi; Horn, Betty C (Journal of Organizational Behavior, 1996)
The present study compared work commitments, overall job satisfaction, intrinsic and extrinsic rewards satisfactions, and organizational and professional turnover intentions of 718 male and female accounting professionals at different career stages. Career stage was measured by professional tenure. The results indicate that there are some differences in work attitudes across career stages for male accounting professionals. Job involvement, organizational commitment, and intrinsic and extrinsic rewards satisfaction are positively related to professional tenure. Organizational turnover intentions are negatively related to professional tenure for male accounting professionals. There are no significant differences in work attitudes across career stages for female accounting professionals, An examination of reasons for differences in work attitude patterns between male and female accountants suggests the need for research to determine whether later career stages (advancement and maintenance) differ for men and women. The results also suggest that future research should consider defining career stage in terms of the overlap between stages defined using alternate career stage measures.
Keywords: dept.acc

Measuring customer satisfaction - Ellis, Lynn W; Curtis, Carey C (Research-technology Management, 1995)
Survey research on measuring customer satisfaction using an index, market share and a lead user confirms that satisfaction must be with the firm as an innovator well as with the innovative service or product. The customer is defined as not only the end user or consumer but as a downstream counterpart of R&D in the same company or in other parts of the distribution chain. For an overall indication of customer satisfaction, measure the firm's responsiveness, its technology (capabilities and products) and product quality/reliability.
Keywords: dept.acc

Speedy research-and-development - how beneficial - Ellis, Lynn W; Curtis, Carey C (Research-technology Management, 1995)
As companies increasingly try to do more with less, one of the key prescriptions in the literature has been to employ practices that shorten time to market, including the time taken in R&D. This article reports on survey research that links cycle times and financial performance, and records executives reactions to the results. The main finding is that the reduced costs of faster cycles fail to show up in improved earnings, and suggests several reasons why this occurs. For companies forced by competition to speed up their cycles, several management methods are given for reducing time with minimal financial impairment.
Keywords: dept.acc